2007
DOI: 10.1080/01650520601065509
|View full text |Cite
|
Sign up to set email alerts
|

Primitive nest architecture and small monogynous colonies in basal Attini inhabiting sandy beaches of southern Brazil

Abstract: The species Mycetophylax conformis, M. simplex and Cyphomyrmex morschi, all belonging to the basal Attini, occur exclusively on beaches along the Atlantic shores of South America. In Brazil C. morschi colonies were found sympatrically with the two Mycetophylax species which, however, had no overlap in their geographic distribution. We recorded species-specific nesting site preferences resulting in a zonal colonization of dune and restinga areas, with distinct preferences in microhabitat choice. After excavatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
3
21
0
1
Order By: Relevance
“…Here, one single circular nest-entrance hole without a well-formed nest mound was observed in C. lectus. Similar structure was also reported to Cyphomyrmex morschi (Klingenberg et al, 2007) and in other Attine genera such as Mycocepurus Forel, Mycetarotes Emery, Trachymyrmex Forel and Sericomyrmex Mayr (Mayhé-Nunes, 1995;Leal et al, 2011). In our study area, two other species of the Cyphomyrmex genus (C. strigatus and C. rimosus) were also observed with similar patterns of external nest architecture as C. lectus.…”
supporting
confidence: 56%
“…Here, one single circular nest-entrance hole without a well-formed nest mound was observed in C. lectus. Similar structure was also reported to Cyphomyrmex morschi (Klingenberg et al, 2007) and in other Attine genera such as Mycocepurus Forel, Mycetarotes Emery, Trachymyrmex Forel and Sericomyrmex Mayr (Mayhé-Nunes, 1995;Leal et al, 2011). In our study area, two other species of the Cyphomyrmex genus (C. strigatus and C. rimosus) were also observed with similar patterns of external nest architecture as C. lectus.…”
supporting
confidence: 56%
“…Data regarding the biology of these species are scarce; hence, we do not know how many alate forms are produced and in which season it takes place. According to Klingenberg et al (2007), there are differences between the three species concerning the number of gynes and males, but the number of alate forms was not correlated to the size of the colony population. During our excavations, we always found gynes and males, but in the summer the number of gynes was higher than in winter.…”
Section: Resultsmentioning
confidence: 99%
“…Two species, M. conformis and M. simplex, are parapatric, and their geographic distributions along the Atlantic coastline do not overlap. Otherwise, M. morschi is sympatric with the other two species, but it does not have common nesting sites, occurring farther from the ocean than M. simplex and M. conformis (Klingenberg et al, 2007). However, Cardoso et al (2010) found M. simplex and M. morschi living in the same phytophysiognomies.…”
Section: Introductionmentioning
confidence: 98%
“…Th e nest architecture of Cyphomyrmex ants is considered geometrically simple compared to that of the Atta and Acromyrmex genera (e.g., Wirth et al 2003;Moser 2006;Klingenberg et al 2007). Some Cyphomyrmex species are not characterized by a conspicuous nest mound as is observed in other Attini genera, such as Mycetarotes, Mycocepurus, Myrmicocrypta, Sericomyrmex, Trachymyrmex (Leal et al 2011) and Atta and Acromyrmex (Wirth et al 2003;Verza et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the nest biology of Cyphomyrmex colonies has been extensively reported (Weber 1940(Weber , 1957Kempf 1964;Weber 1972;Mayhé-Nunes 1995;Leal 1998;Mueller & Wcislo 1998;Schultz et al 2002;Adans & Longino 2007;Silva Junior 2007;Leal et al 2011), little is known about their nesting architecture and population structure. Moreover, considering that Cyphomyrmex contains approximately 37 cataloged species (Price et al 2003), studies on this group are concentrated on relatively few species, such as C. costatus (Weber 1957), C. longiscapus (Mueller & Wcislo 1998;Schultz et al 2002), C. muelleri (Schultz et al 2002) and C. morschi (Klingenberg et al 2007). Although nesting biology in fungus-growing ants is extremely species-specifi c, diverse abiotic and biotic conditions are recognized as key factors that aff ect founding queen nesting behavior, nest architecture and, consequently, nest distribution (Jonkman 1980;Hölldobler & Wilson 1990;Mayhé-Nunes 1995;Leal 1998;Moreira et al 2004a;Soares et al 2006;Vasconcelos et al 2006;Verza et al 2007;Silva et al 2009;van Gils et al 2010).…”
mentioning
confidence: 99%